2022
DOI: 10.1177/09610006221097975
|View full text |Cite
|
Sign up to set email alerts
|

Information disruptions and disruptive information sources in the practice of law: Obstacles in gathering information, through an Israeli lens

Abstract: Lawyers must provide their clients with competent legal services and professional representation. However, in many cases, lawyers find it difficult to attain the necessary information to resolve legal concerns under their inquiry. Disruptive sources of information and faulty information are understudied features of professional information behavior, especially in the information-rich legal profession. The current research aims to explore these complexities and promote a fuller and more realistic understanding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…That information has been compiled into texts, pictures, and videos and disseminated through all kinds of media outlets. Seized by overloaded information from media, the majority increased their news consumption compared to normal ( Bodas et al, 2015 ) and reported media fatigue shortly at the first month of the outbreak ( Solomon, 2022 ).…”
mentioning
confidence: 99%
“…That information has been compiled into texts, pictures, and videos and disseminated through all kinds of media outlets. Seized by overloaded information from media, the majority increased their news consumption compared to normal ( Bodas et al, 2015 ) and reported media fatigue shortly at the first month of the outbreak ( Solomon, 2022 ).…”
mentioning
confidence: 99%